2015
DOI: 10.1097/fjc.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Preconditioning of Myocardial Infarct Size in Dogs Is Triggered by Calcium

Abstract: We showed that exercise induces early and late myocardial preconditioning in dogs and that these effects are mediated through nicotinamide adenine dinucleotide phosphate reduced form (NADPH) oxidase activation. As the intracoronary administration of calcium induces preconditioning and exercise enhances the calcium inflow to the cell, we studied if this effect of exercise triggers exercise preconditioning independently of its hemodynamic effects. We analyzed in 81 dogs the effect of blocking sarcolemmal L-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…49 5 minute periods of rest before a coronary occlusion can initiate a significant protective effect with respect to the cardiac infarct size in dogs. [2][3][4] Pretreatment of EP established by an acute bout of high-intensity intermittent exercise which strenuously and repeatedly stimulates cardiac work was also found to initiate cardioprotective effects against isoproterenol injection or exhaustive exerciseinduced ischemia-hypoxia injury in rat myocardium. 5,6,9,51) In this study, pretreatment of EP at 0.5 hours before exhaustive exercise attenuated the ischemia-hypoxia injury in rat myocardium and decreased the release of cTnI.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…49 5 minute periods of rest before a coronary occlusion can initiate a significant protective effect with respect to the cardiac infarct size in dogs. [2][3][4] Pretreatment of EP established by an acute bout of high-intensity intermittent exercise which strenuously and repeatedly stimulates cardiac work was also found to initiate cardioprotective effects against isoproterenol injection or exhaustive exerciseinduced ischemia-hypoxia injury in rat myocardium. 5,6,9,51) In this study, pretreatment of EP at 0.5 hours before exhaustive exercise attenuated the ischemia-hypoxia injury in rat myocardium and decreased the release of cTnI.…”
Section: Discussionmentioning
confidence: 98%
“…Group EP (Exercise preconditioning group): an EP protocol was designed with minor modifications from previous studies. 2,4) The rats were kept on the animal treadmill. After a warm-up protocol of 15 m/minute, 0% grade for 5 minutes, the speed of the treadmill was increased gradually to 30 m/minute within a 5 minute period.…”
Section: Ethical Approval and Animals: Eight Week Old Malementioning
confidence: 99%
See 1 more Smart Citation
“…29 In a series of studies, Domenech and co-workers explored if intermittent exercise resulted in early and late cardiac precondition. 30 They found that exercise prior to coronary occlusion induces early and late precondition, leading to a reduction in infarct size of 46-52 30,31 and 56-78%, [30][31][32] respectively.…”
Section: Does Exercise Acutely Attenuate Cardiac Ischemia In Patients?mentioning
confidence: 99%
“…The late cardioprotection of EP has been observed by other researchers in myocardial infarction animal models. In a study by Domenech, et al, 16,17) dogs ran on a treadmill for 5 periods of 5 minutes each at 6 km/hour along with 5minute periods of rest as a preconditioning protocol. Results revealed that infarct size induced by I/R injury in EP group significantly decreased in the late preconditioned phase, but the decline in the cardiac function was not significantly improved.…”
Section: Discussionmentioning
confidence: 99%